Application of Vibrational Spectroscopy Supported by Theoretical Calculations in Identification of Amorphous and Crystalline Forms of Cefuroxime Axetil - Alicja Talaczyńska; Kornelia Lewandowska; Anna Jelińska; Piotr Garbacki; Agnieszka Podborska; Przemysław Zalewski; Irena Oszczapowicz; Adam Sikora; Maciej Kozak; Judyta Cielecka-Piontek (The Scientific World Journal)
FT-IR and Raman scattering spectra of cefuroxime axetil were proposed for identification studies of its crystalline and amorphous forms. An analysis of experimental spectra was supported by quantum-chemical calculations performed with the use of B3LYP functional and 6-31G(d,p) as a basis set. The geometric structure of a cefuroxime axetil molecule, HOMO and LUMO orbitals, and molecular electrostatic potential were also determined by using DFT (density functional theory). The benefits of applying FT-IR and Raman scattering spectroscopy for characterization of drug subjected to degradation were discussed.